PHENOMENON OF DEMIKHOV. "TRANSPLANTATION OF VITAL ORGANS IN EXPERIMENT" (1960). HOMOPLASTIC ORGAN TRANSPLANTATION: OF AN ISOLATED HEART, ISOLATED LUNG, KIDNEY, HEAD, HALF OF THE TRUNK, AND THE WHOLE TRUNK - S. P. Glyantsev (Трансплантология (Москва))
The  article  (the third one of five) presents the analysis of the final part  of the third chapter on homoplastic organ transplantation from V.P.  Demikhov's monograph "Transplantation of  vital  organs  in  experiment"  (MedGIz Publ., Moscow,  1960). The article covers the data presented by V.P. Demikhov on his creating the following animal models:  of the isolated  heart  and lung,  kidneys, head, half of the trunk, and the whole  trunk. The isolated  heart  models where  the heart  was positioned in place of the biological one were not successful. The longest  period  of the dog-recipient survival was  15 hours. The  dogs with transplanted lobes of  the  lung  survived up  to 6 days  (there  are no evidence of  a whole lung  transplant in the book); animal-recipients of kidneys survived up to 19 days.  V.P. Demikhov considered that  the graft deaths might be caused  by the biological  tissue  incompatibility between  the donor  and  recipient, and  he stressed the  need  for  its suppression and  the  importance of  choosing the  donor  and  recipient compatible by their  blood group for  successful homoplastic transplantation. By  transplanting the puppies' heads  onto  the cervical  vessels  of  the dogs, starting the experiments from 1954, V.P. Demikhov attempted to prove the role of the central nervous system in the organ engraftment, which was one of the targets  in those experiments. The integration of two bodies, combining their vascular systems, and mixing the blood had two goals: to create the conditions for overcoming the transplantation immunity and to make an animal model  of organ transplant in combination with retaining the organ neurohumoral links. The model of the cross circulation also allowed the formulation and implementation of the organ bank concept in the experiment.